VULNERABILIDADE SOCIOAMBIENTAL A INUNDAÇÕES: ESTUDO DE CASO DAS INUNDAÇÃO POR RIOS E MÁRES PARA O MUNICÍPIO DE SÃO LUÍS, MARANHÃO, BRASIL - RIBEIRO, Priscilla Coelho (2020)
The city of São Luís, Maranhão has intense urbanization process with favorable environmental characteristics coastal flooding printing heterogeneous levels of vulnerability in the territory. The use of indexes is a synthetic way of distinguishing hazards. This study aims to identify the socio-environmental vulnerability of the district of São Luís - MA to flooding in areas that are not susceptible to flooding by water mass movements. The study analyzed the environmental vulnerability of the municipality to flooding (IVA) using the physiographic variables available from official agencies, and social vulnerability to flooding (IVS) using IBGE variables, both classified into five levels of vulnerability, ranging from very low to very high. By weighting the indices, identified the environmental vulnerability to coastal flooding (IVSA). VAT classified 15% of the territory in areas of medium vulnerability and 7.9% as high, identifying district as highly anthropized, with great hydrodynamic influence, located on coastal plains over marshy and marshy deposits, characterized by unconsolidated sediments, highlighting the district: Liberdade, Jaracaty, Alemanha, São Francisco, Ilhinha, Santa Rosa, etc. The IVS presented approximately 14% of the district as highly vulnerable and 14% as medium, being these peripheral or subnormal clusters in a situation of poverty, social helplessness and marginalization, such as: Cidade Olímpica, Vila Embratel, Maracanã, Coroadinho, Liberdade, Anil, São Raimundo, Vila Itamar, etc. The municipality's Socio-Environmental Vulnerability (IVSA) identified 14.9% of the neighborhoods as being highly vulnerable to coastal flooding events, especially in the urban area of the capital. These places showed greater precariousness and socio-environmental deterioration. The sectors of greatest concern are the peripheral ones, with incosolidated infrastructure, resulting from spontaneous and disorderly occupation, occupied by neglected social groups, which are inserted in risky environments.